2021
DOI: 10.1364/oe.434085
|View full text |Cite
|
Sign up to set email alerts
|

Resolution limit in quantum imaging with undetected photons using position correlations

Abstract: Quantum imaging with undetected photons (QIUP) is a unique method of image acquisition where the photons illuminating the object are not detected. This method relies on quantum interference and spatial correlations between the twin photons to form an image. Here we present a detailed study of the resolution limits of position correlation enabled QIUP. We establish a quantitative relation between the spatial resolution and the twin-photon position correlation. Furthermore, we also quantitatively establish the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The resolution limit for the near field configuration depends on the sum of the wavelengths of signal and idler instead of their ratio. [167] Further research on the imaging properties depending on the idler wavelength has been done and shown that the resolution becomes worse as the idler wavelength increases as the number of spatial modes available for imaging is reduced. [165] The theoretical description of quantum spectroscopy and similar schemes is based on the same principle as quantum imaging which is the indistinguishability of paths.…”
Section: Simulation Of Nonlinear Interferometersmentioning
confidence: 99%
“…The resolution limit for the near field configuration depends on the sum of the wavelengths of signal and idler instead of their ratio. [167] Further research on the imaging properties depending on the idler wavelength has been done and shown that the resolution becomes worse as the idler wavelength increases as the number of spatial modes available for imaging is reduced. [165] The theoretical description of quantum spectroscopy and similar schemes is based on the same principle as quantum imaging which is the indistinguishability of paths.…”
Section: Simulation Of Nonlinear Interferometersmentioning
confidence: 99%
“…For the case of identical sources with L = L A = L B , as found in Refs. [21,22], then d min ∝ [L(λ S + λ I )]…”
Section: B Diffraction-limited Resolutionmentioning
confidence: 99%
“…(A3) and the electric field operator at the camera, see Eq. (21). To reach the expression of R in Eqs.…”
Section: Appendix B: Minimum Resolvable Distance In the Paraxial Regimementioning
confidence: 99%
See 1 more Smart Citation
“…We use the term "far-field" in contrast to "near-field", where nearfield interactions can involve evanescent modes and are usually only effective within wavelength-range distances [13]. Hence, resolution of far-field QIUP will be constrained by the diffraction limit [4,[14][15][16]. For the case where the probing wavelength λ I is larger than the detection wavelength λ S , object's information is transferred by propagating idler fields and consequently the transverse spatial resolution in this information is constrained by the idler diffraction limit [14].…”
mentioning
confidence: 99%